The middle Pleistocene extinction of bathyal benthic foraminifera in the South Atlantic (ODP sites 1082 and 1088) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Earth Science at Massey University - O'Neill, Tanya Ann (Massey University, 2005)
The youngest major turnover in deep-sea benthic foraminifera (termed the Stilostomella extinction) is documented in two ODP sites in the South Atlantic Ocean. This study is the first detailed investigation of its kind in this region, and reveals the pulsed decline and eventual extinction of 33 species of elongate, cylindrical benthic foraminifera belonging to the families Stilostomellidae, Pleurostomellidae, and part of the Nodosariidae during the mid-Pleistocene climatic transition (MPT, ~1200 - 600ka). Furthermore, the Stilostomella extinction is limited to elongate species with highly specific apertural characteristics (e.g. cribrate, slit lunate, and hooded with secondary teeth), such as Chrysalogonium, Ellipsoglandulina, and Pleurostomella species, respectively. Micropaleontological and sedimentological data from lower bathyal Sites 1082 and 1088 (1290 m and 2082 m water depth, respectively) provide a proxy record of oceanographic changes in the South Atlantic Ocean through the MPT. This study compares the timing and causes of the Stilostomella extinction between two highly contrasting environmental settings in relation to paleoceanographic history, sediment regime and paleoproductivity. In the South Atlantic, the abundance and accumulation rate of Extinction Group (EG) taxa began to decline between ~ 1070 and 1000 ka at both core sites. The rate of decline was pulsed, with major declines usually associated with cool periods, and partial recoveries during intervening warm periods. The timing of highest occurrences (HOs) was diachronous between sites, and the final Stilostomella extinction datum is marked by the uppermost occurrence of Myllostomella matanzana and Siphonodosaria sagrinensis at ~705 ka in Site 1082, and Myllostomella matanzana and Pleurostomella alternans at ~600 ka in Site 1088. This corresponds with the previously documented global Stilostomella extinction datum within the period of 700 and 570 ka. Detailed comparisons with North Atlantic and Southwest Pacific studies confirm the highly diachronous nature of HOs of EG species, and furthermore, reveal that there is a lead time of ~100 kyr between HOs of the same species in the North Atlantic, compared with the South Atlantic. This study suggests that declines and extinctions at Site 1082 were primarily driven by highly fluctuating food supply associated with increased productivity caused by intensified upwelling during MPT glacial periods. In contrast, extinctions at Site 1088 appear to have been a result of the MPT reorganisation of the global deep-water 'conveyor belt', with δ 13 C gradients revealing that high dissolved oxygen Glacial North Atlantic Intermediate Water (GNAIW) bathed the region during cool periods. Far from a simple response to change in a single parameter, numerous factors have interacted and appear to have caused the demise of the Stilostomella extinction taxa. These factors include encroachment by well-ventilated (high dissolved oxygen) GNAIW, fluctuations in food supply, and possibly winnowing (of the phytodetritus layer) by vigorous bottom currents during MPT glacial periods.
Keywords: South Atlantic Ocean; Foraminifera, Fossil; Benthic animals; Paleoecology -- Pleistocene; Extinction (Biology); Geology, Stratigraphic